Evaluation Composition Nutrients in Plants Lettuce (Lactuca sativa) Hydroponics With Various Formulation Fertilizer - Andila Ricki Syaputra; Fitria; Dayang Safinah Nayan (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Lettuce is a popular leafy vegetable among the community. The expansion and potential of lettuce cultivation require efficient growing techniques. The production of plants using a hydroponic system is closely linked to the availability of nutrient solutions. This study aimed to examine how various fertilizer formulations affect the macronutrient (P, K, Ca, Mg, S) and micronutrient (Fe, Zn, Mn, Cu, B) content of hydroponically grown lettuce plants. A completely randomized design (CRD) was employed, and the Wet Digestion Method was used to prepare dry plant samples by breaking them down with a mixture of strong acids and heat. Nutrient concentrations were then analyzed using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). Statistical analysis of the nutrient data was performed using ANOVA to identify significant differences between treatments. The results indicated that the AB fertilizer and the O38 treatment were the most effective in increasing the majority of nutrients in the plants. Fertilizers with the highest phosphorus content were observed in the AB and O38 treatments, while the highest potassium content was found in the AB and O39 treatments. The highest calcium (Ca) and magnesium (Mg) levels were also recorded in the O38 treatment, highlighting the formulation’s efficiency in supplying macronutrients. Regarding micronutrients, the highest iron (Fe) content was detected in the O37 treatment, whereas the highest zinc (Zn), copper (Cu), and boron (B) contents were found in the AB treatment. This study demonstrated the superiority of the AB fertilizer, which performed best and most consistently. However, the O38 formulation shows potential as a future alternative to commercial AB fertilizers, pending further improvements.